IZIN PRAKTIK TENAGA KESEHATAN TRADISIONAL KOMPLEMENTER YANG BERKEPASTIAN HUKUM - S, Farra Adiba; Mangesti, Yovita Arie (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
A license to practice complementary traditional medicine is the granting of a license to an individual or entity that establishes a health service facility. Everyone who provides complementary traditional medicine services is required to have a practice license. This legal research aims to determine the regulation regarding the license to practice complementary health workers in providing health services in the field of complementary traditional health. The type of research used is normative legal research. The approach used is using the legal approach (statute approach) and the conceptual approach (conceptual approach). Based on this research, shows that the regulation of the practice of complementary traditional health workers refers to the Minister of Health Regulation Number 15 of 2018 concerning the Implementation of Complementary Traditional Medicine. Independent practice must have a practice permit marked by having STRTKT and SIPTKT. As for the agency that establishes (Griya Sehat), it must have an operating permit, where the permit is granted by the district/city health office. On the other hand, with a legal practice permit, traditional complementary health services can be accounted for their benefits and safety so that a health worker can be held accountable for the services provided. In this case, the Government must also regulate and supervise the safety, interests, and protection of clients